Short-circuit Faults in Wind Turbine and Its Protective Measures - ZHANG Yuanlin; ZHAO Yanfeng; GUO Rui; SHENG Jianke; SHE Yue; TAN Shuaixia (Kongzhi Yu Xinxi Jishu)
Along with the rapid development of wind power industry, many significant security issues presented after wind turbines putting into operating. Fire failure caused by electrical short-circuit is one of the major serious security problems currently. Based on the calculation of short-circuit current, the division of electrical protective areas and relative security requirements, it analyzed the mechanism and hazard of short-circuit failure, and proposed security measures in accordance with the relative criteria and the status of the wind power industry.